(untitled) (Archives of Mechanics - Test, 1996)
The effective models (h0, l0) and (h0, l) [7] describing reduction of the in-plane effective moduli of the [0°m /90°n]s cross-ply composites cracked in the internal layer and subjected to in-plane boundary forces are applied to the description of the degradation of the effective Young, Kirchhoff and Poisson moduli of the [0° /90°]s and [0° /903]s glass/epoxy and [0° /902]s graphite/epoxy laminates. lt is shown that the graphs of E1(cd) (cd represents crack density) lie slightly above the Hashin’s curves, while G12(cd) predictions coincide with the curves of Hashin. Evaluation of the off-diagonal terms, i.e. ν12(cd), ν12 (cd) are incorporated in the algorithm. In all comparisons with the experimental results of Groves, Ogin, Highsmith and Reifsnider the predictions of E1(cd) according to the model (h0, l) provide lower bounds, slightly better than the bounds of Hashin. Some predictions of the model (h0, l) are proved to be similar to McCartney’s "generalized-plane-strain" results.